2013
DOI: 10.3109/01480545.2013.866134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sub-acute exposure to TiO2, ZnO and Al2O3nanoparticles on oxidative stress and histological changes in mouse liver and brain

Abstract: Nanomaterials are at the leading edge of the rapidly developing field of nanotechnology. However the information regarding toxicity of these nanoparticles on humans and environment is still deficient. The present study investigated the toxic effects of three metal oxide nanoparticles, TiO2, ZnO and Al2O3 on mouse erythrocytes, brain and liver. Male mice were administered a single oral dose of 500 mg/kg of each nanoparticles for 21 consecutive days. The results suggest that exposure to these nano metallic parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(125 citation statements)
references
References 50 publications
6
105
1
6
Order By: Relevance
“…15 Various studies have shown that ZnO NPs with various shapes, such as rods and spheres, probably cause neurotoxicity due to their ability to access the brain. [16][17][18] Moreover, the olfactory brain route has also been reported as a potential route for ZnO NPs transfer into the brain. 19 However, information regarding the neurotoxic effects of ZnO NPs is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…15 Various studies have shown that ZnO NPs with various shapes, such as rods and spheres, probably cause neurotoxicity due to their ability to access the brain. [16][17][18] Moreover, the olfactory brain route has also been reported as a potential route for ZnO NPs transfer into the brain. 19 However, information regarding the neurotoxic effects of ZnO NPs is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed that metals can induce oxidative stress by generating free radicals and ROS, and the liver and kidney have antioxidant defense systems to protect animals from oxidative stress caused by metals (Jorgensen, 2010). NPs were regarded as one of the main mechanisms involved in induced toxic manifestations in animals, as they can penetrate inside the cytoplasm and nucleus (Shrivastava et al, 2013). The present data demonstrated that total oxidant levels in the serum of rats increased considerably, though total antioxidant levels did not follow this trend, suggesting possible oxidative stress.…”
Section: Total Oxidant and Antioxidant Statusmentioning
confidence: 55%
“…Syama et al (2013) showed that there was a concentration-dependent fall in cell viability, a decrease in antioxidant enzyme levels, and an increase in DNA adduct of the liver of mice following zinc NP exposures. Shrivastava et al (2013) studied the effects of TiO 2 , ZnO, and Al 2 O 3 NPs on oxidative stress in the erythrocytes, liver, and brain of male mice following oral administration of NPs for 21 days. They found that there was significant production of ROS and consecutively antioxidant enzyme activities altered, supporting the present results.…”
Section: Total Oxidant and Antioxidant Statusmentioning
confidence: 99%
“…Some studies have reported that inorganic NPs could pass through the BBB through several pathways ( Fig. 1) and accumulate in different regions of the brain [10][11][12] through different mechanisms and processes. For example, insulin-targeted gold NPs had been reported to cross the BBB by receptor-mediated endocytosis [13], and reduced graphene oxide was found to impair BBB integrity by downregulating the TJ protein occludin and the adherens junction protein β-catenin in vivo [14].…”
Section: The Entry Of Inorganic Nps Into the Cns Via The Bbbmentioning
confidence: 99%